Pengaruh luas pengungkapan informasi, konsentrasi kepemilikan dan diversifikasi pada biaya modal ekuitas: studi pada perusahaan non-keuangan di Indonesia - Ratih Kusumawardhani (Jurnal Siasat Bisnis, 2018)
This study aims to investigate the effect of disclosure, ownership concentration and diversification on the cost of equity capital among non-financial Indonesian firms using IDX data during 2010-2014 periods. This study involves both mandatory and voluntary disclosure that distinguished from previous studies in the context of Indonesia that tend to use only mandatory or voluntary disclosure. This study shows that the disclosure and the concentration of ownership significantly and negativey influence the cost of equity capital. Both mandatory and voluntary disclosure tend to have negative impact on the cost of equity capital. It turns out that the mandatory disclosure has a greater influence on the cost of equity capital than the voluntary disclosure. While, business diversification, that are measured by Herfindahl Index and the number of business segments, significantly and positively affect the cost of equity capital. Lastly, relevant theoretical and practical implications are drawn from this study.Keywords: Disclosure, ownership concentration, business diversification, cost of equity capital